Testosterone Supplementation Increases Lean Mass in Men Undergoing Anterior Cruciate Ligament Reconstruction: A Randomized Controlled Trial. Issue 7 (21st July 2017) - Badash, Ido; Wu, Brian; Berger, Max; Lorenzana, Dan; Lane, Christianne; Sum, Jonathan C.; Hatch, George F. Rick; Schroeder, E. Todd
Objectives: Surgical reconstruction of the anterior cruciate ligament (ACL) is essential for those who wish to resume athletic activity following ACL rupture. However, the trauma of surgical repair and post-operative immobility can exacerbate muscle loss and strength. This study investigated the effect of perioperative testosterone administration on lean mass recovery following ACL reconstruction in men. The effects of testosterone on leg strength and clinical outcome scores were also investigated. We hypothesized that testosterone would increase lean mass and leg strength, and improve clinical outcome scores 6 and 12 weeks after surgery to a greater degree than placebo. Methods: This was a randomized, controlled, double blinded clinical trial comparing testosterone and placebo for recovery from ACL repair. Thirteen male subjects scheduled for ACL reconstruction were randomized into two groups, testosterone (n=6) and placebo (n=7). Participants in the testosterone group received 200 mg of testosterone administration weekly for 8 weeks starting 2 weeks prior to surgery. Participants in the control group received a saline placebo intramuscularly following the same schedule. Both intervention groups underwent standard physical rehabilitation. The primary outcome was change in total lean body mass at 6 and 12 weeks, measured by whole-body dual-energy x-ray absorptiometry. Secondary outcomes were extensor muscle strength measured using a Cybex Dynamometer, and the Tegner Activity Score (TAS) and Knee Injury and Osteoarthritis Outcome Score (KOOS). Results: Total testosterone levels in the blood increased from baseline to an average of 860 ± 254 ng/dL by 1 day prior to surgery and 746 ± 173 ng/dL at 6 weeks post-surgery for the testosterone group. The differences in serum testosterone levels between the placebo and testosterone groups at 1 day prior to surgery and 6 weeks post-surgery were both statistically significant (p<0.001). We found that testosterone increased lean mass by 2.8 ± 1.7 kg from baseline at 6 weeks following surgery, while the placebo group had a decrease in lean muscle mass of 0.1 ± 1.5 kg (p=0.01) (Figure 1). Extensor strength of the non-injured leg had a greater increase from baseline in the testosterone group (20.8 ± 25.6 Nm) than the placebo group (-21.4 ± 36.7 Nm) at 12 weeks (p=0.02). There were no significant differences in injured leg strength or clinical outcome scores throughout the study period. Conclusion: Despite a catabolic environment, acute testosterone supplementation increased lean mass 6 weeks after ACL reconstruction, and strength of the non-injured leg 12 weeks after surgery, to a greater degree than placebo. These results suggest that testosterone may be a novel, useful adjunct to physical therapy for knee surgery rehabilitation by offsetting perioperative muscle loss from surgery and immobility. Larger studies are now necessary to elucidate the effects of perioperative testosterone administration on injured leg strength and clinical outcomes following surgery.